2012
DOI: 10.1155/2012/821347
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Postnatal Followup of Partial Trisomy 13q and Partial Monosomy 10p: A Case Report and Review of the Literature

Abstract: We report prenatal diagnosis and postnatal findings of a fetus with partial trisomy of 13q21.33-qter and partial monosomy of 10p15.3-pter. The mother is a known carrier of a balanced translocation, t(10;13)(p15.3;q21.33), ascertained by history of one miscarriage and two neonatal deaths. The fetal karyotyping on cultured amniocytes showed 46,XX,der(10)t(10;13)(p15.3;q21.33). Oligonucleotide array comparative genomic hybridization (aCGH) defined a 2.339 Mb distal deletion at 10p15.3 (chr10:126,161–2,465,089) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Other chromosome structural rearrangements undetectable by aneuvysion FISH were noted in four cases (cases 14–17) by chromosome analysis. These results support that chromosome analysis is still an important method on detecting balanced and unbalanced structural rearrangements [19]. Furthermore, pCNV were detected in five cases (cases 18–22) by aCGH analysis.…”
Section: Discussionsupporting
confidence: 77%
“…Other chromosome structural rearrangements undetectable by aneuvysion FISH were noted in four cases (cases 14–17) by chromosome analysis. These results support that chromosome analysis is still an important method on detecting balanced and unbalanced structural rearrangements [19]. Furthermore, pCNV were detected in five cases (cases 18–22) by aCGH analysis.…”
Section: Discussionsupporting
confidence: 77%
“…Microarray analysis has been effective to detect all numerical chromosomal abnormalities and to de ne genomic imbalances and rearrangement break points from unbalanced structural chromosomal abnormalities. Identifying carriers of a balanced translocation and tracking unbalanced derivative chromosomes in their fetuses has been a standard procedure for recurrent pregnancy loss [4,13,14]. Earlier studies suggested that POC-CF may be related to particular chromosomal imbalances such as autosomal monosomies which could be incompatible with cell proliferation under in vitro cell culture [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Genetically unbalanced gametes with a partial monosomy and partial trisomy are produced from carriers of a balanced reciprocal translocation (Wei et al, 2012). These unbalanced products are at an increased risk of miscarriage or conception of a phenotypically and molecularly abnormal offspring.…”
Section: Introductionmentioning
confidence: 99%
“…These unbalanced products are at an increased risk of miscarriage or conception of a phenotypically and molecularly abnormal offspring. The genotype-phenotype correlation is inferred by reviewing cases with similar genetic abnormalities in the literature (Wei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%